Pengujian Efektivitas Strategi Schema-Based Instuction (SBI) terhadap Kemampuan Memecahkan Soal Cerita Matematika Penjumlahan dan Pengurangan (Studi pada Siswa Sekolah Dasar Kelas Dua) - Vivi Sutanto; Sri Tiatri; Fransisca I. R. Dewi (Provitae: Jurnal Psikologi Pendidikan, 2010)
Learning to solve mathematical story-problem is beneficial since it emphasizes on thinking process. However, grade two students often experience difficulties in solving the mathematical story-problems. The students’ experiences of difficulties could lead to the reluctance of the students to learn them. Therefore, a strategy is needed to enhance the students’ ability to solve the mathematical story-problem. The purpose of current study is to examine the effectiveness of Schema-Based Instruction (SBI) in enhancing the ability to the grade two primary school students to deal with mathematical story-problem. The participants were six students at WK state primary school in West Jakarta. Results showed that there was an improvement of the participants’ abilities to solve the mathematical story-problems although it was not statistically significant. Further implications were discussed regarding time efficiency and the implementation of the strategy.Keywords: Schema-Based Instruction (SBI), word-problem solving, mathematics, think aloud.